2009
DOI: 10.4049/jimmunol.0802765
|View full text |Cite
|
Sign up to set email alerts
|

The Major Outer Membrane Protein of a Periodontopathogen Induces IFN-β and IFN-Stimulated Genes in Monocytes via Lipid Raft and TANK-Binding Kinase 1/IFN Regulatory Factor-3

Abstract: Surface molecules of pathogens play an important role in stimulating host immune responses. Elucidation of the signaling pathways activated by critical surface molecules in host cells provides insight into the molecular pathogenesis resulting from bacteria-host interactions. MspTL is the most abundant outer membrane protein of Treponema lecithinolyticum, which is associated with periodontitis, and induces expression of a variety of proinflammatory factors. Although bacteria and bacterial components like LPS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…These results were consistent with the typical distribution of caveolin-1 in mammalian cells (Parkin et al, 1996). M␤CD, fillipin III, or nystatin (which deplete or sequester membrane cholesterol) is employed to disrupt the caveolae structure (Foster et al, 2003;Lee et al, 2008Lee et al, , 2009. As shown in Fig.…”
Section: Immunofluorescence and Western Blot Analysis Of Mcav-1 Cellusupporting
confidence: 87%
“…These results were consistent with the typical distribution of caveolin-1 in mammalian cells (Parkin et al, 1996). M␤CD, fillipin III, or nystatin (which deplete or sequester membrane cholesterol) is employed to disrupt the caveolae structure (Foster et al, 2003;Lee et al, 2008Lee et al, , 2009. As shown in Fig.…”
Section: Immunofluorescence and Western Blot Analysis Of Mcav-1 Cellusupporting
confidence: 87%
“…This has led to intense interest in the physiological and clinical roles of B1 cells, which, however, have been difficult to evaluate because clear markers for the human B1 cell population have been lacking for many years. Early efforts to identify human B1 cells using CD5 expression combined with expression of a B cell specific antigen, as in the murine system, have not been revealing because CD5 is expressed on multiple human B cell populations including activated, pre-naïve, and transitional B cells (Freedman et al, 1989; Sims et al, 2005; Lee et al, 2009a; Griffin et al, 2011a). …”
Section: Introductionmentioning
confidence: 99%
“…Our findings strongly indicated that pIRES- ragB-mGITRL may become a potential candidate of DNA vaccine for inhibiting P. gingivalis infection, and GITRL may be a new type of adjuvant (Figure 7). Further studies will focus on how RagB regulates cytokines production in mice, via lipid raft or the surface receptor of innate immunity cells, like the major outer membrane protein of a periodontopathogen, Treponema lecithinolyticum [47], and whether the action of RagB and mGITRL can be blocked by anti-serum from the mice injected with pIRES- ragB-mGITRL .…”
Section: Discussionmentioning
confidence: 99%